Enhancing National Climate Services (ENACTS) for development in Africa. (3rd October 2018) - Dinku, Tufa; Thomson, Madeleine C.; Cousin, Rémi; del Corral, John; Ceccato, Pietro; Hansen, James; Connor, Stephen J.
Abstract : Decision-relevant information on the past climate, recent trends, likely future trajectories, anomalies and associated impacts is a prerequisite for decision-making at different levels. Unfortunately, climate information is often not available or, where it does exist, is inaccessible to those that need it most. The Enhancing National Climate Services (ENACTS) initiative is an ambitious effort to simultaneously improve the availability, access and use of climate information. This is accomplished by working with National Meteorological and Hydrological Services (NMHS) in Africa to develop high-resolution, spatially and temporally complete gridded historical meteorological datasets; produce suites of derived climate information products; and disseminate them through a web-based platform. ENACTS enables the NMHS to provide enhanced services by overcoming the challenges of data quality, availability and access – while at the same time fostering stakeholder engagement and use. The new data products allow for characterization of climate risks at a local scale and offers opportunities to support applications and research. ENACTS has so far been implemented in 10 countries at the national level and at regional levels in East Africa and the West African Sahel. This paper provides an outline of challenges and opportunities in ENACTS implementation, and the potential for scaling up across Africa.